Growth and mortality rates of bigeye tuna Thunnus obesus (Perciformes: Scombridae) in the central Atlantic Ocean - Zhu, Guoping (2009)
Age and growth parameters were estimated for bigeye tuna Thunnus obesus Lowe, 1839 sampled from China longline fisheries in the central Atlantic Ocean from October 2002 to July 2003 and from August 2004 to March 2005. The von Bertalanffy growth parameters were estimated at L∞=217.9 cm fork length, k=0.23 year-1, and t0=-0.44 year. The total mortality rate (Z) was estimated to be from 0.82 to 1.02, the fishing mortality (F) and the natural mortality were 0.54 year-1 and 0.39 year-1, respectively. The exploitation ratio (E) was 0.35. This study provides the detailed estimates of growth and mortality rate for bigeye tuna in the central Atlantic Ocean, which can be used as biological input parameters in further stock evaluations in this region. However, age analysis, additional validation of the size composition and stock structure are needed for future studies.